Evaluation of angoff and mapmark standard-setting procedures and considerations in setting cut scores of college admission test - Villas, Jonas P. (College of Education, University of the Philippines Diliman, 2018)
The elements of evaluation focused on internal, procedural and external validity, and modelled the effects by means of Many-Facet Rasch Model (MFRM) using 3282 students'data. The study also looked into the considerations of the 63 members of the standard-setting panel and the management committee in recommending and finalizing the cut score. The findings of the study shows that the Mapmark methods has better inter-rater reliability than the Angoff method and the cut scores produced by both methods are statistically different with score that is lower than that of the Angoff methods thus, facilitating a higher passing rate.